2023
DOI: 10.17711/sm.0185-3325.2023.022
|View full text |Cite
|
Sign up to set email alerts
|

Team sports as a protective factor against mental health problems and suicidal ideation in adolescents

Abstract: Introduction. Adolescents who practice sports have better mental health indicators. Objective. To analyze the association between different types of physical activity (systematized exercise, individual, and collective sports), mental health, and suicidal ideation in adolescents. Method. We conducted a cross-sectional study with 666 Brazilian adolescents (14-19 y.o.) attending high schools and selected using random cluster sampling. The mental health indicators analyzed were evaluated through the Self Reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, the results content did not show a notable impact. The study concluded that social identity plays a critical role in the functioning and success of sports teams, although the significance of social identity can change based on the team's values and objectives [36,37]. Further research indicated that boys participating in team sports exhibited fewer symptoms of common mental disorders and had lower levels of mental health issues than their physically inactive peers [32].…”
Section: Emotional Wellness: Cultivating Resilience Through Team Part...mentioning
confidence: 95%
See 2 more Smart Citations
“…However, the results content did not show a notable impact. The study concluded that social identity plays a critical role in the functioning and success of sports teams, although the significance of social identity can change based on the team's values and objectives [36,37]. Further research indicated that boys participating in team sports exhibited fewer symptoms of common mental disorders and had lower levels of mental health issues than their physically inactive peers [32].…”
Section: Emotional Wellness: Cultivating Resilience Through Team Part...mentioning
confidence: 95%
“…Adolescent engagement in team sports has been positively linked to mental health improvements. Research conducted by Machado-Oliveira et al demonstrates that boys participating in team sports exhibit reduced symptoms of mental disorders, have fewer mental health issues, and show lower instances of suicidal thoughts than those who are not active [37]. Further, Larocca et al's study indicates that involvement in team sports decreases the risk of depression and suicidal thoughts across all youths, including LGBTQ individuals.…”
Section: Spiritual Wellness: Finding Purpose In Team Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, school-based team sports and sports clubs provide vital social and psychological support for mental health [34,35]. Research on youth athletes revealed that strong group identification enhances self-worth, commitment, and effort [36,37]. Boys in team sports exhibited fewer mental health issues than inactive peers, underscoring the positive impact of team sports on mental health [32].…”
Section: Emotional Wellness: Cultivating Resilience Through Team Part...mentioning
confidence: 99%